Dynamics and performances in the international trade of Romania's agri-food products, by the processing level - Mirela-Adriana Rusali (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
The research aims at analyzing the factors of export growth of Romania's agri-food products on the world market during the period 2001-2013. The analysis used statistics for Romania's foreign trade and world trade in nominal terms, by main groups of products aggregated by codes 01-24 of the Harmonised System. The results show changes in the structure of agri-food trade flows of import and export by processing degree, evolution of trade balance and structure of export growth, highlighting the comparative performance of pre-accession Romanian and post-accession.
Keywords: 330; agri-food trade; processing sector; post-accession